PEMAHAMAN TENTANG HAKIKAT DIRI: KAJIAN KRITIS TERHADAP TATTVABODHA KARYA ŚAṄKARĀCĀRYA: Kajian Kritis Terhadap Tattvabodha Karya Śaṅkarācārya - Gupta, Gede Endy Kumara (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This study critically explores Śaṅkarācārya's interpretation of the True Self (Ātma) within the framework of Advaita Vedānta as presented in Tattvabodha. It examines the non-dualistic perspective that affirms the identity of the Self and the Supreme Reality (Brahman), while addressing the epistemological challenges involved in understanding this unity. Tattvabodha is presented as outlining the foundational step toward liberation (mokṣa) and self-realization. The teachings are not merely metaphysical but also provide solutions to dualistic dilemmas, carrying ethical implications that foster empathy and an awareness of universal Oneness. This analysis underscores the enduring relevance of Śaṅkarācārya's insights in contemporary life, highlighting their timeless significance and opening pathways for further interdisciplinary research.